2023
DOI: 10.1039/d2cc05207e
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical sulfinylation of phenols with sulfides: a metal- and oxidant-free cross-coupling for the synthesis of aromatic sulfoxides

Abstract: The site-selective C-H functionalization of arenes is of indisputable importance in organic chemistry. Herein, we demonstrated an electrochemical regioselective oxidative cross-coupling towards the direct C(sp2)-H sulfinylation of phenols with sulfides...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In the last decade, electro‐organic synthesis has emerged as a useful method for performing advantageous organic transformations [17] to achieve specific oxidative or reductive reactions such as decarboxylation, [18a] alkene bifunctionalization, [18b] rearrangements, [18c] annulations, [18d] and C−C or C‐heteroatom bond formation [18e–i] . In 2021, Lei et al .…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, electro‐organic synthesis has emerged as a useful method for performing advantageous organic transformations [17] to achieve specific oxidative or reductive reactions such as decarboxylation, [18a] alkene bifunctionalization, [18b] rearrangements, [18c] annulations, [18d] and C−C or C‐heteroatom bond formation [18e–i] . In 2021, Lei et al .…”
Section: Methodsmentioning
confidence: 99%
“…A variety of substrates, including C2-substituted benzothiophene S-oxides and C3-substituted benzothiophene S-oxides, were successfully used in the arylated reaction to realize the C-H bond functionalization of free phenols. However, when using 4- Recently, the Banerjee group [59] further developed an electrochemical sulfinylation of free phenols 162 with sulfides 163 under catalyst-and oxidant-free conditions. The aromatic sulfoxides 164 were obtained with 38-65% yields in an undivided cell equipped with a graphite anode and a nickel cathode at a constant current of 15 mA, using n-Bu 4 NPF 6 as the electrolyte at room temperature (Scheme 27).…”
Section: Othersmentioning
confidence: 99%
“…Control experiments suggested that the electrochemical sulfonated reaction was proposed to initiate via the anodic oxidation of phenol to generate carbocation, which was then attacked by the nucleophilic sulfide to generate the desired product. Recently, the Banerjee group [59] further developed an electrochemical sulfinylation of free phenols 162 with sulfides 163 under catalyst-and oxidant-free conditions. The aromatic sulfoxides 164 were obtained with 38-65% yields in an undivided cell equipped with a graphite anode and a nickel cathode at a constant current of 15 mA, using n-Bu4NPF6 as the electrolyte at room temperature (Scheme 27).…”
Section: Othersmentioning
confidence: 99%
“…The most prevalent approach to achieve sulfoxides involves the oxidation of organic sulfides using peroxides, 11 a,b oxone, 11 c IBX/Et 4 NBr, 11 d aerobic photocatalysis, 11 e,f and electrochemical techniques. 12 Some recent and relevant reports for the synthesis of sulfoxides are shown in Scheme 1. Jiang et al have developed an efficient sulfoxidation reaction using thiosulfates and diaryl iodonium salts in the presence of eosin Y, DIPEA, and Zn(OAc) 2 under green LED irradiation (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%